Nanomaterials in PCR: exploring light-to-heat conversion mechanisms and microfluidic integration - Samaneh Shamsian; Abu Bakar Siddique; Vahid Kordzadeh-Kermani; Luna de la Vega Tejuca; Francisco Falcone; Mallar Ray; Seyed Nezameddin Ashrafizadeh; Sergio Omar Martínez Chapa; Marc J. Madou; Masoud Madadelahi (Microsystems & Nanoengineering)
Abstract As a popular process in molecular-based diagnostics, polymerase chain reaction (PCR) can be employed for amplifying small amounts of DNA/RNA from different sources such as tissue, cells, peripheral blood and so on. Thanks to the unique physicochemical characteristics of nanomaterials and their progress, researchers have been encouraged to employ them as suitable candidates to address the PCR optimization challenges for enhancing efficiency, yield, specificity, and sensitivity. In nanoparticle-assisted PCR (nanoPCR), different nanoparticles (NPs) such as carbon nanotubes (CNTs), graphene, quantum dots (QDs), and gold (Au) might be used. Among different nanoPCR assays, photothermal PCR has emerged as a technique leveraging the excellent light absorption and heat conversion capabilities of nanomaterials. In addition to presenting recent advances in nanoPCR, this review also delves into the specific use of nanomaterials for photothermal PCR, including their applications in microfluidics as one of the best platforms for miniaturization of diagnostic techniques. Different types of NPs used in PCR are comprehensively examined, and detailed charts and tables are provided that outline features such as optimal concentration and size. The appropriate choice of nanomaterials for enhancing light conversion to heat in PCR applications is discussed. Finally, the related challenges and future trends are explored.